VALIDITY OF PRIMARY SCHOOL EXAMINATION AS A PREDICTOR OF SECONDARY SCHOOL EXAMINATION SCORE AMONG PUBLIC SECONDARY SCHOOL STUDENTS KENYA - Agingu, Eunice Atieno (International Journal of Research -GRANTHAALAYAH, 2018)
The purpose of this study was to determine the validity of KCPE as a predictor of KCSE scores among public secondary school students in Kisii central Sub-county, Kenya. This study was guided by a conceptual framework where KCPE was the independent variable and KCSE the dependent variable. It adopted Correlational and Ex-post-facto research designs. The study population was 3,897 KCSE candidates from 55 public secondary schools. Stratified random sampling based on school type and size was used to select 16 public secondary schools for the study. Saturated sampling was employed to include all KCSE candidates whose KCPE marks were available in each sampled school, yielding a sample of 1,391 students. Data used included 2006 KCPE scores and 2010 KCSE scores of the same students under study. Data was collected using a researcher made pro forma. It was analyzed quantitatively using correlations and regression analyses. Results showed a strong positive Pearson’s correlation coefficient (r=0.693; n=1391; p < 0.05) between KCPE and KCSE scores. It recommended that; KCPE should continue to be used as selection tool for secondary school admission and school evaluation using KCSE examination scores should be based on students’ past KCPE scores.